Phytopatological properties of symbiotic Rhizoctonia solani strains associated to orchids - Oros, Gyula; R. Széki, Eszter; Naár, Zoltán; Magyar, Donát (Acta Agraria Debreceniensis, 2014)
The mycobiota of the Orchidarium of ELTE Botanical Garden (Budapest) has been studied applying aerobiological methods and isolating of tissue samples taken from 92 individuals of sixty orchid species. Among isolated basidiomycetaceous fungi 13 strains of Rhizoctonia solani were surviving in axenic culture. These symbiotic R. solani strains proved to be pathogenic on 24 cultivated plant species at varying degree. The symptoms of disease caused by R. solani strains isolated from orchids did not differ from that caused by reference strains. Three groups of strains could be separated regardless of their source or aggressivity. The host plants clustered into two groups, and their taxonomic position had no role in this respect. In general, we can assume that orchid associated Rhizoctonia strains are potential plant pathogens, and removed or withdrawn orchid stools should be treated as hazardous waste.